An investigation of the effects of infertility on Women's quality of life: a case-control study - Katayoun Bakhtiyar; Ramin Beiranvand; Arash Ardalan; Farahnaz Changaee; Mohammad Almasian; Afsaneh Badrizadeh; Fatemeh Bastami; Farzad Ebrahimzadeh (BMC, 2019)
Abstract Background Human instinctively desire to have offspring. Infertility can cause painful emotional experiences throughout the life mainly known as quality of life impairment. This study aimed to investigate the impact of infertility on a woman's quality of life. Methods A number of 180 infertile and 540 fertile women participated in this matched case-control study. The cases were selected through a combination of multistage stratified and cluster sampling methods. For each infertile woman three fertile women were randomly selected. The data gathering instrument consisted of demographic variables and the WHOQOL-BREF questionnaire. Data collection was conducted through interview with participants. The multivariate marginal model and SPSS software 21 were used for data analyses with a significance level of 0.05. Results The results of the multivariate modeling show infertility can potentially affect various aspects of women's quality of life such as physical health (p <  0.001), mental health (p <  0.001), social health (p <  0.001) and the total score of quality of life (p <  0.001) significantly. Conclusion An infertile woman practice a relatively lower scores in QOL sub-scales of mental, physical and environmental health; while they experience a higher social health score than a fertile woman.